The InsP3 receptor calcium release channel - Foskett, J. Kevin (Henry Stewart Talks, 2007)
The inositol trisphosphate receptor signaling system, Dynamic properties of cytoplasmic Ca2+ signals, Structural properties of the InsP3R, Patch clamp electrophysiology of the InsP3R channel, Permeation properties of the channel, Channel gating regulation by Calcium and InsP3, Channel mechanisms that account for graded Ca2+ release, Isoform specific differences in channel gating, Channel regulation by ATP and interacting proteins